2014
DOI: 10.1038/bjc.2013.815
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fibrinogen is a prognostic and predictive biomarker in malignant pleural mesothelioma

Abstract: Background:To investigate the clinical utility of pretreatment plasma fibrinogen levels in malignant pleural mesothelioma (MPM) patients.Methods:A retrospective multicenter study was performed in histologically proven MPM patients. All fibrinogen levels were measured at the time of diagnosis and clinical data were retrospectively collected after approval of the corresponding ethics committees.Results:In total, 176 MPM patients (mean age: 63.5 years±10.4 years, 38 females and 138 males) were analysed. Most pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 23 publications
5
43
0
Order By: Relevance
“…Fibrinogen and circulating activin A levels demonstrated a similar prognostic power in the present study. Furthermore, a significant difference between the non-epithelioid and epithelioid subgroups was only found in activin A levels but not in fibrinogen concentrations [40].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Fibrinogen and circulating activin A levels demonstrated a similar prognostic power in the present study. Furthermore, a significant difference between the non-epithelioid and epithelioid subgroups was only found in activin A levels but not in fibrinogen concentrations [40].…”
Section: Discussionmentioning
confidence: 75%
“…We previously identified fibrinogen as a novel prognostic biomarker in MPM [40]. Thus, we performed a correlation analysis between fibrinogen and circulating activin A which revealed a significant relationship between these two parameters.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that fibrinogen (Fib), a major protein in the blood clotting process, is associated with cancer 6 . Although recent studies have reported that plasma Fib was related to cancer progression and prognosis in various cancers [7][8][9] , the role of plasma Fib in EC remains controversial [10][11][12] . Recently, two metaanalyses revealed that plasma Fib was a prognostic indicator in patients with EC 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen, a glycoprotein synthesized by liver epithelium, plays an essential role in the coagulation cascade, converting to fibrin monomers and ultimately forming the fibrin polymers7. Previous studies indicated that elevated preoperative fibrinogen level might induce higher malignance progression and poor prognosis5,6. However, few studies have investigated the predictive impact of preoperative fibrinogen levels in ESCC patients.…”
Section: Introductionmentioning
confidence: 99%